ANALISIS DAMPAK IMPLEMENTASI SURAT EDARAN WALIKOTA MALANG NOMOR 8 TAHUN 2021 DALAM RANGKA MEMERANGI EMISI MIKROPLASTIK DI KOTA MALANG - Purwaningsih, Roosi Wahju; Arvianti, Eri Yusnita; Sasmito, Cahyo; Lestari, Wulan Puji (Universitas 17 Agustus 1945 Surabaya, 2025)
Waste has become a complex problem faced by all countries worldwide, including Indonesia. As a byproduct of human activity, waste is produced daily in increasing quantities along with population growth, changes in consumption patterns, and technological developments. The method used in this study is a quantitative method with a Structural Equation Modelling (SEM) approach. The results of the study related to factors influencing community behavior in efforts to address microplastic waste in Malang City found that policy standards and targets play a significant role in shaping community behavior towards reducing microplastic emissions, and contribute positively to supporting the microplastic reduction program, and are a key factor in the success of socialisation. The characteristics of the implementers play a crucial role in the effectiveness of implementation. The implementation of Circular Letter No. 8/2021 of the Mayor of Malang has been proven to be effective in encouraging the reduction of microplastic emissions.